Corporate Strategy Formulation for Poultry Equipment Division PT Medion: Directional, Portfolio, and Parenting Strategy - Hirawan, Bubun Setiawan; Toha, Mohamad (The Indonesian Journal of Business Administration, 2013)
Rapid growth in poultry industry provides opportunities and threats for Medion. With multiple businesses to manage, Medion needs effective corporate strategy to maximize its value. What is the appropriate directional strategy for Medion? How Medion should manage its portfolio and how Medion should organize its poultry equipment businesses?. To understand the situation, external and internal analysis must be done using STEEP analysis and Porter’s Five Forces. Corporate strategy formulation includes directional, portfolio, and parenting strategy. How Medion responds to this situation will be answered under directional strategy. Portfolio strategy will be done using BCG Matrix and GE Business Screen. Parenting framework is appropriate for Medion as parent company. Medion can put influence on each its business unit and assess whether it can create or destroy value. The framework assess critical success factors of each business, available parenting opportunities, and parenting characteristics, then assess the fit and misfit between these elements.  Data is collected by secondary data, interview and survey to assess situation and formulate strategies. Quantitative survey on Medion’s customers is done on questionnaire using judgmental sampling. The suitable directional for Medion is concentric growth because the company has strong competitiveness and the market is attractive. In portfolio strategy, Medion needs to develop star business because currently it lacks one. The ideal candidate is brooding business. Meditech business should be liquidated and the resource allocated on other businesses. As parent company, Medion has to develop parenting opportunity to improve brooding business from edge of heartland category into heartland and keep the whole ownership of feeder, drinker, and brooding business. Through these strategies, PT Medion should be able to respond correctly to the changing environment of poultry industry by investing, growing, maintaining, and even harvesting the right businesses. Finally, the company will achieve higher business growth and produce sustainability on long term basis.   Keywords: corporate strategy, grand strategy, portfolio strategy, parenting framework